Pertanggungjawaban Pidana terhadap Anak yang Berkonflik dengan Hukum Tanpa Hak Menjual Narkotika: Studi Putusan Nomor 28/PidSus.Anak/2025/Pn.Mdn - Tesa Lonika Br. Tarigan; Marlina; Wessy Trisna (Jurnal Hukum Lex Generalis, 2026)
Criminal liability of children in narcotics offenses requires a balance between law enforcement and child protection. This study aims to analyze the legal framework governing narcotics offenses, the criminal liability of children and the judges' legal reasoning in Decision of the Medan District Court Number 28/PidSus.Anak/2025/PN.Mdn. This research employed a normative juridical method using statutory and case approaches. The findings indicate that a child may be held criminally liable if the child has reached the minimum age of criminal responsibility as stipulated by law, possesses the capacity for criminal responsibility and the elements of the offense are proven. However, the imposition of sanctions must prioritize the best interests of the child. Therefore, the Government should harmonize the Narcotics Law with the Juvenile Criminal Justice System Law to ensure greater legal certainty and stronger protection for children.